Development of Interactive Media for Listening skill and Speaking skills Assisted by Lectora Inspire and Plotagon Story - Shefia, Nilla; Ahsanuddin, Mohammad (Universitas Yudharta Pasuruan, 2023)
The success of learning must be connected to the role of the media, especially in language learning that requires interactive media so that students can actively participate in the learning process. The purpose of the interactive media development research assisted by Lectora Inspire and Plotagon Story is to support the learning of listening skill and speaking skills for grade V students of MI Rahmat Sa'id Jombang. The subjects of this study were 22 students of VA MI Rahmat Sa'id. This research is a Research and Development (RnD) research using the Borg and Gall model, which is modified into six stages. The result of the development of this media is in the form of an android application that contains learning materials for listening skills and speaking skills by taking material about al-mihnah (profession). The results showed that this interactive media is very suitable for use when learning, as evidenced by the average value of expert tests of 81% and user tests of 92.4%, categorized as